(untitled) - Harley, John P.; John P. Harley (Australia,United States, 2007)
Organized by chapter, students will find Chapter Overviews that link the chapter to homeostasis,Chapter Outlines, Key Terms, and Review Exercises. This learning resource also offers Points to Ponder questions designed to stimulate use of material in the chapter as a starting point for critical thinking that guides the student to further learning. Clinical Perspectives, common applications of the physiology under consideration, and Experiments of the Day, simple hands-on activities, further enhance the learning process
Keywords: Human physiology